Victim Impact Statements: Their Effect on Court Outcomes and Victim Satisfaction in New York, 1988-1990 - Davis, Robert C. ([Verlag nicht ermittelbar], 1991)
The purpose of this data collection was to assess the effects of victim impact statements on sentencing decisions and on victim satisfaction with the criminal justice system. Victims were randomly assigned to one of three experimental conditions: (1) Victims were interviewed, with an impact statement written and immediately distributed to the prosecutor, defense attorney, and judge on the case, (2) Victims were interviewed to assess impact but no statement was written, and (3) Victims were assigned to a control condition in which there was no interview or statement. Subsequent interviews evaluated victims' perceptions of their role in the proceedings and their satisfaction with the outcome. Data were also recorded on charges filed against the defendants (both the arraignment and final charges), sentences, and special conditions of sentences. Standard demographic information was gathered as well. The remaining variables fall into two categories. The first category includes questions about the defendant(s) in the case. For all defendants in each case (up to six per victim) the researchers recorded information on the nature and severity of the arraignment charges and final charges, and on the sentence received. Additional information was recorded for the first and second defendants in a case. This included information on special conditions of the sentence such as a drug treatment program or restraining order. Orders to pay restitution were noted. Also recorded was information on the defendant's status with the criminal justice system, including number of prior convictions and number of open cases against the defendant. Finally, whether the Victim Impact Statement appeared in the assistant district attorney's file on the case and whether the statement had been opened were noted. The second category of variables includes information about the victim's reactions to the crime and the criminal justice system. Victims were asked to assess the impact the crime had on them in terms of physical injury, financial losses, psychological effect, and behavioral effect (i.e., changes in behavior resulting from the experience). They were also questioned about their experiences with the criminal justice system. The researchers inquired about their participation in the sentencing decision, their satisfaction with the outcome, and how they felt they had been treated by various court officials. Victims were asked whether they felt that court officials were aware of and were concerned about the effect the crime had on them. They were also asked whether victims should have a greater role in the court proceedings and whether court officials should be aware of victim impact as part of the sentencing procedure. Finally, the researchers investigated whether the victims believed that going to court was a waste of time.